1999
DOI: 10.1515/cclm.1999.135
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Oxidized LDL in the First Phase of Life

Abstract: The study presents a comparison of data concerning lipid metabolism and lipid oxidation (oxidative stress) in children at the time of their birth and 3 months later, as well as of their mothers at the time of delivery, compared to a control group of non-pregnant women of the same age. The data confirm that labour represents an oxidative stress for both mother and child; it is expressed as a significant increase of malondialdehyde concentration in mothers immediately after delivery in comparison with non-pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Steinerova et al [18] found a significantly higher peroxide level in mothers after delivery, while Rogers et al [16] found lower peroxides levels in cord blood. Thus, our findings confirm both these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Steinerova et al [18] found a significantly higher peroxide level in mothers after delivery, while Rogers et al [16] found lower peroxides levels in cord blood. Thus, our findings confirm both these studies.…”
Section: Discussionmentioning
confidence: 97%
“…4) They display an acute phase response in acutely ill patients, often increasing significantly within hours to days after an event. 5) They may have different influences on atherogenesis, at least in experimental models, in which IgMs, which are more likely to be enriched in natural antibodies present even at birth (26) seem to be atheroprotective, but IgGs seem to be atherogenic, except perhaps in response to vaccination, in which they may be associated with atheroprotection (10,26,34,35,(37)(38)(39). In humans, we have recently shown that IgM OxLDL autoantibodies and IgM apoB-ICs were associated inversely with the presence of angiographically determined CAD, whereas IgG OxLDL autoantibodies and IgG apoB-ICs were positively associated (40).…”
Section: Relationship Of Oxpl/apob Lp(a) and Oxldl Biomarkers To Dementioning
confidence: 99%
“…The investigators found that anti-oxLDL IgA correlated closely with aCL (p < 0.0001) but IgM and IgG had weak or no association, respectively. Steinerova et al [148] measured anti-oxPL in infants and observed that breast-fed babies, during the first 3 months, had much lower levels (p < 0.001) and less DNA breaks than those not breast-fed. As noted later, CL easily oxidizes in air so that many reports actually measure aOxCL, not aCL.…”
Section: Introductionmentioning
confidence: 99%